2012
DOI: 10.1088/0957-4484/23/50/505501
|View full text |Cite
|
Sign up to set email alerts
|

Improved gas sensing activity in structurally defected bilayer graphene

Abstract: Graphene is a two-dimensional material with a capability of gas sensing, which is here shown to be drastically improved by inducing gentle disorder in the lattice. We report that by using a focused ion beam technique, controlled disorder can be introduced into the graphene structure through Ga(+) ion irradiation. This disorder leads to an increase in the electrical response of graphene to NO(2) gas molecules by a factor of three in an ambient environment (air). Ab initio density functional calculations indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…They can act as nucleation sites for the onset of deformation, when subjected to stress [2][3][4] . When exposed to chemical functional groups, defects can also behave as highly reactive sites and efficiently trap different molecules 5,6 . A rich variety of dislocations have recently been observed in 2D crystals such as graphene, hexagonal boron nitride and transition metal dichalcogenides (TMDs) [7][8][9][10][11][12] .…”
mentioning
confidence: 99%
“…They can act as nucleation sites for the onset of deformation, when subjected to stress [2][3][4] . When exposed to chemical functional groups, defects can also behave as highly reactive sites and efficiently trap different molecules 5,6 . A rich variety of dislocations have recently been observed in 2D crystals such as graphene, hexagonal boron nitride and transition metal dichalcogenides (TMDs) [7][8][9][10][11][12] .…”
mentioning
confidence: 99%
“…36,37 The gas molecules NH 3 and NO 2 are well-documented in the literature on graphene gas sensors. 34,38,39 While CVD graphene is highly sensitive to NO 2 , it shows relatively low sensitivity to NH 3 . 31,34,40 We therefore use NO 2 -doped graphene as our sensing element for the NH 3 tests to increase sensitivity to NH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The change in chemical, structural or electronic surface composition by doping provides many opportunities for creating surfaces with tailored physicochemical properties, for tuning the electronic properties of semiconductor material, and for enhanced detection of a target analyte. Hajati et al reported graphene with a capability of gas sensing was shown to be drastically improved by inducing gentle disorder in the lattice through Ga + ion interaction [13]. Rare earth elements doping in metaloxide semiconductors to improve gas sensitivity have been reported by Li et al (Pr doped in SnO 2 [14] and Ce doped ZnO [15]), by Cheng et al (Y-doped SnO 2 prismatic hollow nanofibers) [16], by Song et al (Ce element doped in SnO 2 ) [17] and so on.…”
Section: Introductionmentioning
confidence: 99%